2018
DOI: 10.1016/j.jsps.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito and tick repellency of two Anthemis essential oils from Saudi Arabia

Abstract: The essential oils (EOs) of (Am) and (As) (Asteraceae) were extracted from the aerial parts of the plants by hydrodistillation, and their chemical compositions were analyzed using GC-FID and GC-MS. Fifty-six components representing 85.5% of the oil composition of were identified, and the major components were-pinene (17.1%) and -eudesmol (13.8%). Forty-one components representing 86% of the oil composition of were identified, and the major component was -eudesmol (12.8%) Laboratory bioassays were conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…aegypti mosquitoes revealed BTEO to have a MED (see Experimental) for repellency of 0.625 ± 0.109 mg/cm 2 ; however, this indicated weak repellency compared to the reference standard repellent, DEET (N,N-diethyl-3-methylbenzamide) (MED = 0.008 ± 0.002 mg/cm 2 ). The repellency of BTEO was significantly less (F = 10.741; df = 4.10; P < .001) than the other three oils, Anthemis scorbicularis essential oil (AMEO), 39 Caryopteris × clandonensis essential oil (CCEO), 40 and Prangos platychlaena essential oil (PPEO), 41 but all these oils were less potent than DEET ( Figure 1). Additionally, we have tested some of the predominant compounds in BTEO for their repellency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti mosquitoes revealed BTEO to have a MED (see Experimental) for repellency of 0.625 ± 0.109 mg/cm 2 ; however, this indicated weak repellency compared to the reference standard repellent, DEET (N,N-diethyl-3-methylbenzamide) (MED = 0.008 ± 0.002 mg/cm 2 ). The repellency of BTEO was significantly less (F = 10.741; df = 4.10; P < .001) than the other three oils, Anthemis scorbicularis essential oil (AMEO), 39 Caryopteris × clandonensis essential oil (CCEO), 40 and Prangos platychlaena essential oil (PPEO), 41 but all these oils were less potent than DEET ( Figure 1). Additionally, we have tested some of the predominant compounds in BTEO for their repellency.…”
Section: Resultsmentioning
confidence: 99%
“…aegypti mosquitoes. Response observed with blue tansy essential oil (BTEO) was compared with that of known MED values, Anthemis scorbicularis essential oil (AMEO), 39 Caryopteris × clandonensis essential oil (CCEO), 40 Prangos platychlaena essential oil (PPEO), 41 and to the standard insect repellent DEET (N,N-diethyl-3-methylbenzamide). Means followed by the same letter are not significantly different based on the Tukey-Kramer method; α = 0.05, with human subjects, n = 3. was compared with response to known strong attractants, tea tree oil (TTO), 25 Tetradenia riparia essential oil (TREO) 26 and known mild attractants, two sources of mastic gum essential oils (MGEO-1 and MGEO-2).…”
Section: Essential Oil Analysismentioning
confidence: 99%
“…Suganya (et al 2013) showed promising results for larvicidal activity of the M. koenigii ethanolic extract through the green synthesis of silver nanoparticles (LC 50 = 22.03 ppm; LC 90 = 55.95 ppm). Krishnamoorthy et al (2015) obtained LC 90 below 90 ppm for the essential oil of Murraya exotica leaves against ROMANO et al 2018;YUSUFOGLU et al 2018). The interference of natural products in metabolic pathways may be observed by the inactivation of the acetylcholine binding site, growth-inhibiting hormones, calcium channel blockade in nerve cells and activation of pathways that lead to apoptosis and/or increase in the nitric oxide production (ISMAN 2006;KABIR et al 2013;OLIVEIRA et al 2017;GUIMARÃES-DE-OLIVEIRA et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the mosquito was introduced in the colonial period, being responsible for the transmission of urban yellow fever (YF) (TAUIL 2010). In addition to the transmission of YF and dengue, in its five serotypes (WHO 2009;MUSTAFA et al 2015), it has been considered the main vector of the chikungunya virus (CHIKV), according to Albuquerque et al (2012), and zika virus (ZIKV), according to Bayes (2009) and Gourinat et al (2015), which were also present a repellent effect on feeding and/or oviposition (KRISHNAMOORTHY et al 2015, SOONWERA;PHASOMKSOLSIL 2017, OLIVEIRA et al 2017, YUSUFOGLU et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation